Community-Based Interventions as Opportunities to Increase HIV Self-Testing and Linkage to Care Among Men Who Have Sex With Men – Lessons From Ghana, West Africa - Abubakari, Gamji M'Rabiu; Turner, DeAnne; Ni, Zhao; Conserve, Donaldson F.; Dada, Debbie; Otchere, Amma; Amanfoh, Yaw; Boakye, Francis; Torpey, Kwasi; Nelson, LaRon E. (Frontiers in Public Health, 2021)
MSM in Ghana encounter challenges in accessing HIV services and may experience barriers to HIV self-testing due to multiple forms of stigma present in health care settings. We worked with community-based organization partners to implement three interventions that successfully engaged and retained MSM which provides an opportunity for linkage to self-testing and medical care. These interventions were (1) Many Men Many Voices (3MV) a locally-led culturally grounded group-level HIV prevention program, (2) Auntie’s Corner: a mobile-app based connecting MSM to health monitoring by a registered nurse and (3) HIV Education, Empathy, & Empowerment (HIVE3): a mobile-app based peer support intervention for MSM living with HIV. The 3MV intervention may be effective in improving HIV self-testing due to its effectiveness in engaging MSM, increasing HIV testing, and improving MSM understanding of the need for HIV testing. The utilization of apps like Auntie’s Corner could positively impact HIV self-testing among MSM because it increases contact with nurses and reporting of symptoms. In HIVE3, participants expressed appreciation of the security and privacy that protects their identities as MSM and the peer mentors’ abilities to make referrals to the nurses in Auntie’s Corners. The confidentiality component has proven key among MSM and connecting MSM to self-testing through apps to report their process and receive care could increase utilization. Together, we show the efficacy of using the community-engaged process in reaching and engaging highly stigmatized populations like Ghana and sub-Saharan Africa, and its potential in increasing HIV self-testing and linkage to HIV care.